PERANAN PEMBELAJARAN PPKN DALAM MEMBENTUK SISWA YANG DEMOKRATIS DI SMP MUHAMMADIYAH BAORDING SCHOOL PALOPO - Puspita Hartono; Firman Umar; Najamuddin Najamuddin (Phinisi Integration Review, 2023)
This study intends to find out (i) know the role of Civics learning in forming democratic students at SMP Muhammadiyah Baording School Palopo, to (ii) the learning process of PPKn at SMP Muhammadiyah Boarding School Palopo, to (iii) find out the supporting and inhibiting factors in forming students who democratically at the Muhammadiyah Boarding School Middle School Palopo. This type of research uses qualitative research, which in this study describes the actual data obtained through the interview process. There are two data analysis techniques used in this study, namely, data reduction, namely summarizing the selection of basic rights according to the research focus of presenting data and drawing conclusions. Data collection techniques used are interview observations, data documentation.The results of this study show that (1) Civics learning has a role in forming democratic students at the Muhammadiyah Boarding Middle School in Palopo. (3) the learning process has been running starting from the introductory, core and closing activities. This has been going quite well (2) the supporting and inhibiting factors in forming democratic students at Muhammadiyah Boarding School Palopo Middle School. This can be seen from the facilities and infrastructure. one of the things that supports the learning process in the classroom so that students are not bored with the learning process packaged by the teacher while the obstacles in forming democratic students include the teacher having difficulty being less thorough in determining democratic values and attitudes of teachers who are less creative, students who difficult to navigate and the facilities and infrastructure are still inadequateStudi ini bermaksud guna mengetahuai (i) mengetahui peranan  pembelajaran PPKn dalam membentuk siswa yang demokatis  di SMP Muhammadiyah Baording School  Palopo, untuk (ii) Proses pembelajaran PPKn diSmp Muhammadiyah Boarding School Palopo, untuk (iii) mengetahui faktor pendukung dan penghambat dalam membentuk siwa yang demokratis  di SMP Muhammadiyah Boarding School  Palopo. Jenis penelitian ini menggunakan penelitian kualitatif , dimana pada penelitian ini mendiskripsikan data actual yang diperoleh melaui proses wawancara. Teknik analisis data yang digunakan penelitian ada dua yaitu, Reduksi data  yaitu merangkum memilih hak-hak pokok sesuai dengan fokus penelitian  penyajian data dan penarikan kesimpulan. Teknik pengumpulan data yang digunakan yaitu pengamatan  wawancara , data dokumentasi.Hasil studi ini memperlihatkan bahwa (1)  Pembelajaran ppkn memiliki peranan dalam membentuk siswa yang demokratis di Smp  Muhammadiyah Boarding Palopo. (3) proses  pembelajaran sudah bejalan dengan mulai dari kegiatan pendahuluan ,inti dan penutup Hal ini sudah berjalan dengan cukup baik (2) faktor pendukung dan penghambat dalam membentuk siswa yang demokratis di SMP Muhammadiyah Boarding School Palopo   Hal ini dapat dilihat dari sarana dn prasarana merupakan slah satu hal yang mendukung proses pembelajaran dalam kelas sehingga peserta didik tidak jenuh dengn proses pembelajaran yang di kemas oleh guru   sedangkan penghambat dalam membentuk siswa yang demokratis di antaranya adalah guru mengalami kesulitan kurang teliti dalam menentukan  nilai dan sikap demokratis  guru yang kurang kreatif ,siswa yang sulit di arahkan  serta sarana dan prsarana yang masih kurang memadai